The Effect of Blended Learning on Integrated Social Sciences Learning Outcomes in Middle School Students - Bayu Prasetio; I Komang Winatha; Widya Hestiningtyas (Universitas Sang Bumi Ruwa Jurai, 2023)
The existence of the covid-19 pandemic that has hit Indonesia since February 2020 seems to be able to change the face of Indonesian education significantly. One of the things that has arisen as a result of the pandemic is the application of the Blended Learning model. The changing learning process makes the implementation of learning not maximal in class so that it causes a decrease in student learning outcomes. This study aims to determine the effect of blended learning on integrated social sciences learning outcomes in class VII and VIII students of SMPN 1 Palas, South Lampung. This study uses descriptive verification research methods with ex post facto and survey approaches. The population in this study were students of class VII and VIII of SMPN 1 Palas with a total of 294 students. The sampling technique in this study was probability sampling using simple random sampling. The sample calculation uses the Slovin formula, so that there are 169 respondents. Data collection techniques using observation techniques, interviews, documentation, and questionnaires. Hypothesis testing was carried out using a simple linear regression test. Based on the results of the research that has been done, it is concluded that there is a positive and significant effect of blended learning on learning outcomes of Integrated Social Sciences of 8.64 percent.